Evolving treatment options for melanoma brain metastases. Issue 13 (October 2015) - Ajithkumar, Thankamma; Parkinson, Christine; Fife, Kate; Corrie, Pippa; Jefferies, Sarah
Summary: Melanoma is a leading cause of lost productivity due to premature cancer mortality. Melanoma frequently spreads to the brain and is associated with rapid deterioration in quality and quantity of life. Until now, treatment options have been restricted to surgery and radiotherapy, although neither modality has been well studied in clinical trials. However, the new immune checkpoint inhibitors and molecularly targeted agents that have been introduced for treatment of metastatic melanoma are active against brain metastases and offer new opportunities to improve disease outcomes. New challenges arise, including how to integrate or sequence multiple treatment modalities, and current practice varies widely. In this Review, we summarise evidence for the treatment of melanoma brain metastases, and discuss the rationale and evidence for combination modalities, highlighting areas for future research.